A post disaster capacity building model in Peru. Issue 1 (March 2016) - Rivera-Holguín, Miryam; Velázquez, Tesania; Morote, Roxana
Abstract : This paper presents a model of a capacity building intervention, which encompasses twophases: reception and familiarity (a process of getting to know people to beyond their problems) and community mobilisation. This intervention was conducted with 65 participants from Chincha (Peru) urban and rural areas after the earthquake of 15 August 2007, highlighting a community intervention that was based on the content and methodology generated during the sessions. It is grounded in the recognition of local capacities and putting collective action into practice, through workshops and art to enhance culture and identity and empower participants. The 65 participants were able to mobilise their communities to design and create 17 murals and signboards. The main achievements of this model of intervention were the progressive withdrawal of external professionals involved, the development of personal skills of community leaders (e.g. self efficacy, organisation), and the systematic increase of leadership and community participation.